IMPLEMENTASI CINEMA THERAPY â€œSATU PERSEN-INDONESIAN LIFE SCHOOLâ€ PADA PERILAKU MALADAPTIF SANTRIWATI TMI PUTRI PONDOK PESANTREN AL-AMIEN PRENDUAN - siti Khotijah; Siti Wasilatur Rahma (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2023)
One of the technological developments in guidance and counseling in schools is Cinema Therapy or film therapy. According to Brigit Wolz, Ph.d., MFT, psychotherapist and film therapist from Oakland United States, Cinema Therapy is made based on allusions (metaphors) where the tropes are presented through words, symbols, character characters, themes, and conflicts. Cinema Therapy is a modern technique in group counseling interventions that is suitable for adults, adolescents and children and is carried out by watching movies or videos with group members that aim to add insight to the counselor to overcome problems that are in accordance with the problems experienced by the counselor. So that the focus of research in this study is to find out how the implementation of cinema therapy "One Percent–Indonesian Life School" on the Maladaptive Behavior of TMI female students of Pondok Pesantren Al-Amien Prenduan and to find out how the results of the implementation of Cinema Therapy One Percent-Indonesian Life School on Maladaptive Behavior Santriwati TMI Putri P ondok Pesantren Al-Amien Prenduan. The research method in this study uses a qualitative approach with the type of case study research (case studies). With data collection techniques using interviews, observations and documentation. Where as a research subject, the researcher took information from santriwati class III Regular H and homeroom teacher class III Regular H. The results of the research obtained in this study are, after the implementation of Cinema Therapy "Satu Persen-Indonesian Life School" found better changes in the maladaptive behavior of students of class III Regular H, namely, enthusiasm for learning, good socialization ability, akhlakul karimah, minimizing violations of cottage discipline, and self-confidence.